(untitled) (Revista Internacional de Folkcomunicação, 2020)
This article is an ethnographic research on “CANDEEIRO”, printed by ASA (Articulação Semiárido Brasileiro). The investigation reflects on Candeeiro’s communication proposal as a communicative experience that does not focus on information, but on an educational communication dimension in the rural area of ​​the Northeast. The Candeeiro is produced from the local cultures of the sertão in its coexistence with drought. We problematize the concept of Systematization of experiences that underlies the communicative practice to understand how the ASA and the people of the researched locality experience the production of the newspaper in this relationship between communication and inclusion of cultural habits. The field survey lasted eight months and took place in Lagoa do Juá, Ceará. Communication; Culture; Systematization of Experience.